RENTAL INFORMATION SYSTEMS Topas Galeria HOTEL ROOMS IN USING MICROSOFT ACCESS 2000 - Serly Serly; Don Elsafitra, SKom (Jurnal Sistem Informasi, 2005)
Information is one  of the most important resources in an enterprise. The manager always uses the information to perform their duties, so that the subject of information management is not something new. The new is the ease of obtaining an accurate and timely information. Innovation that enables this capability is the electronic computer. Organizations become increasingly aware that information is an important source of strategic power and the computer can process these resources. Topas galleria hotel as one company engaged in  the tourism accommodation that provides lodging and needs to eat, drink, and general support services for managed commercially, are experiencing barriers to obtaining accurate and timely information. Constraints are included on room rentals in an integrated system so that the need for companies to menggunkan process of computerization as a data processing system data processor on room rentals.